2021
DOI: 10.1093/biosci/biab107
|View full text |Cite
|
Sign up to set email alerts
|

Data Science in Undergraduate Life Science Education: A Need for Instructor Skills Training

Abstract: There is a clear demand for quantitative literacy in the life sciences, necessitating competent instructors in higher education. However, not all instructors are versed in data science skills or research-based teaching practices. We surveyed biological and environmental science instructors (n = 106) about the teaching of data science in higher education, identifying instructor needs and illuminating barriers to instruction. Our results indicate that instructors use, teach, and view data management, analysis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…This allows students to revisit earlier time points to make direct measurements for comparative analysis or make additional observations. Data analysis and the related computer skills required for this are a critical component of modern scientific research that is typically under-emphasized in early college biology coursework [42] . By providing students with simple-to-use analysis tools, students are empowered to look closer at what is occurring and draw more interesting conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…This allows students to revisit earlier time points to make direct measurements for comparative analysis or make additional observations. Data analysis and the related computer skills required for this are a critical component of modern scientific research that is typically under-emphasized in early college biology coursework [42] . By providing students with simple-to-use analysis tools, students are empowered to look closer at what is occurring and draw more interesting conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Three Research-Based Quantitative Reasoning Modules for Introductory Organismal Biology Laboratories management, analysis, and visualization and view these skills as important, a lack of space in the curriculum was identified as a barrier to integration of more of these skill-building activities (7). Furthermore, this survey revealed that learning coding was less valued by instructors as a skill for undergraduate students, although instructors were themselves interested in receiving training on how to teach coding skills.…”
Section: Learning Objectivesmentioning
confidence: 97%
“…In addition, CoPs provide the means for faculty to learn about contemporary breakthroughs within their discipline and pedagogical best practices, while adapting a resource so that it can be implemented in a specific context (Addis et al, 2013;Sirum & Madigan, 2010). By providing expert support during implementation, CoPs can also function as meaningful professional development models for faculty and answer calls for instructor training (Emery et al, 2021;Holmberg et al, 2021). CoPs can also structure the development and validation of assessment instruments, the collection of crossinstitutional data, and the dissemination of assessment findings (Kleinschmit et al, 2021).…”
Section: Leveraging Cops To Foster Oer Developmentmentioning
confidence: 99%